Plan-Do-Study-Act (PDSA) Cycle for Antimicrobial Stewardship in Trauma Centre: Implementation Research for Rational Use of Antimicrobials in Orthopedic Patients - Dr Niveditha Krishnappa (International Journal of Infectious Diseases)
Introduction: One of the most effective measures to reduce unnecessary antibiotic exposure and its adverse outcomes is the implementation of antibiotic stewardship program (ASP). Our Advanced Trauma Centre (ATC) is a tertiary referral centre in Northern India. We adopted a PDSA cycle as a time series analysis of rational antimicrobial use. The objectives of study were to measure the change in antibiotic use per patient in different phases of PDSA cycle, rational use of antibiotics, change in antibiotic prescribing practices and compliance with antibiotic guidelines. Methods: After the ethics committee approval, the study was collaborated with department of Orthopedic, Microbiology and Hospital Administration. We designed antimicrobial stewardship form specific for ATC. We implemented ASP for orthopaedic patients in the trauma centre from March 2019 in 4 phases using the implementation Model, Plan–Do–Study–Act (PDSA) cycle. We have analysed 3 phases (till May 2023) and 4th phase is continuing from July 2023.The primary source of patient information: patient demographics, cause and nature of injury, route, dose, and frequency of antimicrobials prescribed, length of therapy(LOT), defined daily dose (DDD), duration of hospital stay, culture reports, was from inpatient case file and hospital information system. We made various strategies across the phases are as follows: antibiotic protocol for open and closed fractures, educating trauma nurses and resident doctors (bed-side bite-size educative sessions), prospective audit and feedback, created WhatsApp group involving orthopaedics faculty and residents to post randomly selected Orthopaedic cases for regular ASP rounds, Microbiology Report tracking and intensification of infection control measures. Results and Discussion: The total number of patients in 3 Phases were 261, 210, 149 respectively. The mean age was similar across the phases: 35.3 years, 35.7 years and 36.3 years. Culture-based-antimicrobial-prescriptions increased from 0.7% (Phase I) to 1% (Phase II) to 19.7% (Phase III). The proportion of patients with closed fractures who received antibiotics apart from surgical prophylaxis was reduced from 92.6% to 74% to 50%. Compliance with prophylaxis guidelines in the study was 11% in Phase 1, 26.5% in Phase 2, and 55.4% in Phase 3. The DDD per 1000 patient days was 1212.8, 677.8, and 742.6 over phases. The Duration of Treatment per 1000 patient days in Phase 1 was 800.9, in Phase 2 was 686.4, and in Phase 3 was 783.5. The LOT per 1000 patient days in Phase 1 was 442.8, in Phase 2 was 331.4, and in Phase 3 was 544.7. Conclusion: In a tertiary care centre, referred cases of multiple open fractures with potential risk of infection is a considerable challenge for rational antibiotic use, we have demonstrated that the implementation of an efficient ASP with the help of an effective PDSA cycle can drastically better prescribing practices to improve treatment outcomes.